Research and Development of Computer Control Technology Experiment System Based on Network. Issue 2 (August 2021) - Wu, Qiong; Li, Mingjun; Chen, Deming
Abstract: The state has sufficient funds to invest in education. However, schools in some remote areas still do not have enough funds to set up offline teaching laboratories. In addition, the lack of experimental resources in the school also led to the failure of some teaching courses [1]. Many schools spend a lot of effort to build computer-based control laboratories. Even many schools have developed control technology test-bed in order to save cost. However, due to the large volume of the test bed, its handling is very inconvenient. In order to solve the above problems, experts propose to establish an electronic laboratory in the network. In order to help the experimental courses of mechanical and electrical majors in some schools go smoothly, the research and development of the experimental system of computer control technology based on network has been in progress. This paper briefly introduces the design scheme of network control experiment system and the operation platform of software. In the end, the problems that should be paid attention to in the operation of the system are also put forward.